FACTORS AFFECTING STUDENTS’ LEARNING SUCCESS IN BLENDED COURSES IN TERTIARY EDUCATION- A LITERATURE REVIEW - Nguyễn, Thị Thu Hiền (NHÀ XUẤT BẢN ĐẠI HỌC QUỐC GIA HÀ NỘI, 2019)
This paper investigates the factors that may inﬂuence blended learning success in tertiary education. Although blended learning has gained its popularity in many countries all over the world, it is still a quite novel approach of learning and teaching in Vietnam; therefore, it is essential to determine which factors that may interfere students’ learning in this new approach in order to make some timely preparations and improvements and make it more eﬀective. By carrying out a literature review on a number of articles which have been done during the period of time from 2000 to 2018 from two main databases: ERIC (Educational Resource Information Centre) and ProQuest, some crucial factors have been revealed. After reading these full articles carefully, the researcher have found some common factors and divided them into some major categories including learner dimension (students’ culture of learning as well as their knowledge and skills for independent learning, computer literacy skills), instructor dimension (teachers’ knowledge and skills in employing a blended learning environment, teachers’ attitude and perception), institution dimension (institutional support, technical infrastructure), design dimension (perceived usefulness and perceived easy to use, learning activities), and other factors (educational and monetary resources, culture-related factors). The result of this research will be benefcial not only to the students and the teachers but also to all the stakeholders when applying or planning to apply blended learning approach. Bài báo này tìm hiểu các yếu tố có thể có ảnh hưởng đến việc thành công trong việc học theo mô hình học tập kết hợp của sinh viên ở bậc đại học. Mặc dù mô hình học tập kết hợp đã khá phổ biến trên rất nhiều nước trên thế giới, nó vẫn còn là một mô hình dạy và học khá mới ở Việt Nam. Vì vậy, việc tìm hiểu các yếu tố có thể can thiệp vào việc học của sinh viên theo mô hình này là rất cần thiết để có những sự chuẩn bị và cải thiện kịp thời để làm nó hiệu quả hơn. Bằng việc tổng hợp từ rất nhiều bài báo đã được thực hiện trong giai đoạn từ năm 2000-2018 từ hai nguồn dữ liệu chính: ERIC và ProQuest, một vài yếu tố quan trọng đã được tìm ra. Sau khi đọc các bài báo này một cách kĩ lưỡng, nhà nghiên cứu đã tìm ra một số yếu tố phổ biến được đề cập và đã chia chúng thành các hạng mục lớn bao gồm các yếu tố về người học (văn hóa học tập cũng như kiến thức và kĩ năng cần thiết cho việc học độc lập, kĩ năng sử dụng máy tính), các yếu tố về người dạy (bao gồm kiến thức và kĩ năng để dạy trong môi trường học tập kết hợp, thái độ và quan điểm của giáo viên), các yếu tố về tổ chức (sự hỗ trợ của tổ chức, cơ sở hạ tầng), các yếu tố về thiết kế chương trình học (tính hữu ích và dễ sử dụng, các hoạt động học tập) và một số yếu tố khác (như nguồn tiền dành cho giáo dục, các yếu tố liên quan đến văn hóa). Kết quả của nghiên cứu này sẽ hữu ích không chỉ với sinh viên và giáo viên mà còn đối với tất cả những người liên quan khi áp dụng và chuẩn bị áp dụng mô hình học tập kết hợp.